Silica particle, silica sol, polishing composition, polishing method, method for producing semiconductor wafer, and method for manufacturing semiconductor device
Patent Information
- Application Number
- JP2024230287
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2020-01-28
- Filing Date
- 2024-12-26
- Publication Date
- 2025-03-14
- Estimated Expiration
- 2041-01-25
AI Technical Summary
【0015】 本発明のシリカ粒子は、2次凝集を抑制し、分散安定性に優れ、研磨組成物として用いた場合に、平滑な表面の被研磨体が得られ、研磨性能の安定性に優れる。また、本発明のシリカゾルは、シリカ粒子の2次凝集を抑制し、分散安定性に優れ、研磨組成物として用いた場合に、平滑な表面の被研磨体が得られ、研磨性能の安定性に優れる。更に、本発明の研磨組成物は、平滑な表面の被研磨体が得られ、研磨性能の安定性に優れる。
Smart Images

Figure 2025036640000001
Abstract
Description
[Technical field]
[0001] The present invention relates to silica particles, a silica sol, a polishing composition, a polishing method, a method for manufacturing a semiconductor wafer, and a method for manufacturing a semiconductor device. [Background technology]
[0002] Polishing methods using polishing liquids are known as methods for polishing the surfaces of materials such as metals and inorganic compounds. In particular, in the final polishing of prime silicon wafers for semiconductors and reclaimed silicon wafers, and in chemical mechanical polishing (CMP) for planarizing interlayer insulating films during semiconductor device manufacturing, forming metal plugs, forming buried wiring, etc., the surface condition has a significant effect on the semiconductor characteristics. Therefore, the surfaces and end faces of these parts are required to be polished with extremely high precision.
[0003] In such precision polishing, a polishing composition containing silica particles is adopted, and colloidal silica is widely used as the abrasive grains, which are the main component. Depending on the manufacturing method, colloidal silica is known to be produced by pyrolysis of silicon tetrachloride (fumed silica, etc.), by deionization of alkali silicate such as water glass, and by hydrolysis and condensation reaction of alkoxysilane (generally called the "sol-gel method").
[0004] Many studies have been conducted on methods for producing silica particles. For example, Patent Documents 1 to 4 and Non-Patent Documents 1 and 2 disclose methods for producing silica particles by hydrolysis and condensation reactions of alkoxysilanes.
[0005] Generally, silica particles in a silica sol obtained by hydrolysis and condensation of an alkoxysilane exhibit various shapes such as spherical, cocoon-like, and irregular shapes immediately after synthesis, as disclosed in Non-Patent Document 1.
[0006] Patent Document 1 discloses cocoon-shaped silica particles, and Patent Document 2 discloses irregularly shaped (elongated) silica particles.
[0007] However, when cocoon-shaped or irregularly shaped silica particles such as those disclosed in Patent Documents 1 and 2 are used as a polishing composition, the polishing composition has excellent polishing power, but it causes scratches on the object to be polished, so that it is difficult to obtain an object to be polished with a smooth surface. In addition, when cocoon-shaped or irregularly shaped silica particles are used as a polishing composition, the silica particles are prone to change in physical properties during storage or use, such as secondary aggregation, and the polishing performance is poor in stability. To solve these problems, more spherical silica particles are required.
[0008] When silica particles having a large particle size are used as a polishing composition, although the polishing power is excellent, the polishing composition has a problem that the polished object is scratched, and therefore the polished object cannot have a smooth surface. In addition, the silica particles are prone to change in physical properties during storage or use, such as secondary aggregation or sedimentation, and the polishing performance is poor in stability. To solve these problems, silica particles having a smaller particle size are required.
[0009] Patent Documents 3 and 4 and Non-Patent Document 2 disclose silica particles that are nearly spherical and have a small particle size, but do not disclose silica particles that are nearly spherical and have a small particle size, and therefore cannot be said to be sufficient to solve the above-mentioned problems of not being able to obtain a polished body with a smooth surface and of poor stability of polishing performance. [Prior art documents] [Patent documents]
[0010] [Patent Document 1] Japanese Patent Application Publication No. 11-60232 [Patent Document 2] Japanese Patent Publication No. 4-187512 [Patent Document 3] International Publication No. 2013 / 073025 [Patent Document 4] Japanese Patent Publication No. 61-209910 [Non-patent literature]
[0011] [Non-Patent Document 1] "Technology and characteristics of high-purity colloidal silica" Shinichi Sugita, JETI, Vol. 61, No. 3, pp58-61, (2013). [Non-Patent Document 2] "Controlled growth of monodisperse silica spheres in the micron size range" Stöber, Journal of Colloid and Interface Science, Vol. 26, No. 62-69, (1968). Summary of the Invention [Problem to be solved by the invention]
[0012] The present invention has been made in view of the above circumstances, and aims to provide silica particles which suppress secondary aggregation, have excellent dispersion stability, and are suitable for polishing, a silica sol containing the silica particles, and a polishing composition containing the silica sol. Another aim of the present invention is to provide a polishing method suitable for polishing, a method for producing a semiconductor wafer including the polishing method, and a method for producing a semiconductor device including the polishing method. [Means for solving the problem]
[0013] As a result of extensive investigations, the present inventors have found that the above-mentioned problems can be solved by increasing the circularity coefficient of silica particles, and have thus completed the present invention.
[0014] That is, the gist of the present invention is as follows. [1] Silica particles, having an average circularity coefficient of 0.90 or more and a standard deviation of the circularity coefficient of 0.05 or less, as measured by a field emission scanning electron microscope. [2] Silica particles having an average circularity coefficient of 0.90 or more as measured by a field emission scanning electron microscope, and an average Heywood diameter of 30 nm or less as measured by a field emission scanning electron microscope. [3] Silica particles having an average circularity coefficient of 0.90 or more as measured by a field emission scanning electron microscope, and an average aspect ratio of 1.20 or less as measured by a field emission scanning electron microscope. [4] Silica particles according to any one of [1] to [3], having an average Heywood diameter of 20 nm or less as measured by a field emission scanning electron microscope. [5] Silica particles according to [1], [2] or [4], having an average aspect ratio of 1.20 or less as measured by a field emission scanning electron microscope. [6] The silica particles according to [4], wherein the standard deviation of the Heywood diameter is 3.00 nm or less. [7] Silica particles according to [5], wherein the standard deviation of the aspect ratio is 0.15 or less. [8] Silica particles according to any one of [1] to [7], having a metal impurity content of 5 ppm or less. [9] Silica particles according to any one of [1] to [8], which contain a tetraalkoxysilane condensate as a main component.
[10] A silica sol comprising the silica particles according to any one of [1] to [9].
[11] A polishing composition comprising the silica sol according to
[10] .
[12] A polishing method comprising a step of polishing with the polishing composition according to
[11] .
[13] A method for producing a semiconductor wafer, comprising a step of polishing the wafer with the polishing composition according to
[11] .
[14] A method for producing a semiconductor device, comprising a step of polishing the device with the polishing composition according to
[11] . Effect of the Invention
[0015] The silica particles of the present invention suppress secondary aggregation and have excellent dispersion stability, and when used as a polishing composition, a polished object with a smooth surface is obtained, and the polishing performance is excellent in stability.In addition, the silica sol of the present invention suppresses secondary aggregation of silica particles and has excellent dispersion stability, and when used as a polishing composition, a polished object with a smooth surface is obtained, and the polishing performance is excellent in stability.Furthermore, the polishing composition of the present invention can obtain a polished object with a smooth surface, and the polishing performance is excellent in stability.
[0016] The polishing method of the present invention is suitable for polishing. Furthermore, the method for producing a semiconductor wafer and the method for producing a semiconductor device of the present invention include the polishing method of the present invention, and therefore have excellent production stability for the object to be polished. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0017] The present invention will be described in detail below, but the present invention is not limited to the following embodiments and can be modified and practiced in various ways within the scope of the gist. In addition, when the expression "~" is used in this specification, it is used as an expression including the numerical values or physical property values before and after it.
[0018] (Silica particles) The silica particles of the present invention have an average circularity coefficient of 0.90 or more as measured by a field emission scanning electron microscope. When the average circularity coefficient of the silica particles of the present invention is 0.90 or more, the secondary aggregation of the silica particles is suppressed, the dispersion stability of the silica particles in the dispersion liquid is excellent, and when the silica particles are used as a polishing composition, a polished body with a smooth surface is obtained, and the silica particles have excellent polishing performance stability.
[0019] The average circularity coefficient of the silica particles of the present invention is preferably 0.90 to 0.99, more preferably 0.92 to 0.98. When the average circularity coefficient of the silica particles of the present invention is 0.90 or more, as described above, the secondary aggregation of the silica particles is suppressed, the dispersion stability of the silica particles in the dispersion is excellent, and when the silica particles are used as a polishing composition, a polished body with a smooth surface is obtained, and the silica particles have excellent polishing performance stability. In addition, when the average circularity coefficient of the silica particles is 0.99 or less, the silica particles can be easily produced.
[0020] The standard deviation of the circularity coefficient of the silica particles of the present invention is preferably 0.05 or less, more preferably 0.01 to 0.05, and even more preferably 0.02 to 0.04. When the standard deviation of the circularity coefficient of the silica particles of the present invention is 0.05 or less, the secondary aggregation of the silica particles is suppressed, the dispersion stability of the silica particles in the dispersion is excellent, and when the silica particles are used as a polishing composition, a polished body with a smooth surface is obtained, and the silica particles have excellent polishing performance stability. In addition, when the standard deviation of the circularity coefficient of the silica particles of the present invention is 0.01 or more, the silica particles can be easily produced.
[0021] The average value of the Heywood diameter of the silica particles of the present invention is preferably 30nm or less, more preferably 5nm to 20nm, and even more preferably 6nm to 19nm.When the average value of the Heywood diameter of the silica particles of the present invention is 30nm or less, when the silica particles are used as a polishing composition, a polished object with a smooth surface can be obtained, and the silica particles have excellent polishing performance stability.In addition, when the average value of the Heywood diameter of the silica particles of the present invention is 5nm or more, the storage stability of the silica sol is excellent.
[0022] The standard deviation of the Heywood diameter of the silica particles of the present invention is preferably 3.00nm or less, more preferably 0.10nm to 3.00nm, and even more preferably 0.50nm to 2.50nm. When the standard deviation of the Heywood diameter of the silica particles of the present invention is 3.00nm or less, the secondary aggregation of the silica particles is suppressed, the dispersion stability of the silica particles in the dispersion is excellent, and when the silica particles are used as a polishing composition, a polished body with a smooth surface is obtained, and the silica particles have excellent polishing performance stability. In addition, when the standard deviation of the Heywood diameter of the silica particles of the present invention is 0.10nm or more, the silica particles can be easily produced.
[0023] The average value of the major axis of the silica particles of the present invention is preferably 31 nm or less, more preferably 6 nm to 21 nm, and even more preferably 7 nm to 20 nm. When the average value of the major axis of the silica particles of the present invention is 6 nm or more, the storage stability of the silica sol is excellent. In addition, when the average value of the major axis of the silica particles of the present invention is 31 nm or less, when the silica particles are used as a polishing composition, a polished object having a smooth surface is obtained, and the silica particles have excellent stability of polishing performance.
[0024] The average short diameter of the silica particles of the present invention is preferably 29 nm or less, more preferably 4 nm to 19 nm, and even more preferably 5 nm to 18 nm. When the average short diameter of the silica particles of the present invention is 4 nm or more, the storage stability of the silica sol is excellent. In addition, when the average short diameter of the silica particles of the present invention is 29 nm or less, when the silica particles are used as a polishing composition, a polished object with a smooth surface is obtained, and the silica particles have excellent polishing performance stability.
[0025] The average aspect ratio of the silica particles of the present invention is preferably 1.20 or less, more preferably 1.01 to 1.20, and even more preferably 1.02 to 1.18. When the average aspect ratio of the silica particles of the present invention is 1.20 or less, secondary aggregation of the silica particles is suppressed, the dispersion stability of the silica particles in the dispersion is excellent, and when the silica particles are used as a polishing composition, a polished body with a smooth surface is obtained, and the silica particles have excellent polishing performance stability. In addition, when the average aspect ratio of the silica particles of the present invention is 1.01 or more, the silica particles can be easily produced.
[0026] The standard deviation of the aspect ratio of the silica particles of the present invention is preferably 0.15 or less, more preferably 0.01 to 0.15, and even more preferably 0.02 to 0.14. When the standard deviation of the aspect ratio of the silica particles of the present invention is 0.15 or less, the secondary aggregation of the silica particles is suppressed, the dispersion stability of the silica particles in the dispersion is excellent, and when the silica particles are used as a polishing composition, a polished body with a smooth surface is obtained, and the silica particles have excellent polishing performance stability. In addition, when the standard deviation of the aspect ratio of the silica particles of the present invention is 0.01 or more, the silica particles can be easily produced.
[0027] The circularity coefficient, Heywood diameter, major axis, minor axis and aspect ratio of the silica particles of the present invention and their standard deviations are measured using a field emission scanning electron microscope. Specifically, the measurements and calculations are performed under the following conditions.
[0028] A dispersion of silica particles is dropped onto a silicon substrate and dried, and the silicon substrate is irradiated with an electron beam at an acceleration voltage of 5 kV using a field emission scanning electron microscope. A secondary electron image is then taken at a magnification of 50,000 to 200,000 times so that the total number of silica particles is 80 or more, and the Heywood diameter, major axis, minor axis, circularity coefficient, and aspect ratio of all silica particles are measured, and their average values and standard deviations are calculated. At this time, the concentration of silica particles in the dispersion may be appropriately adjusted.
[0029] The shape of the silica particles is determined as described below. Whether or not two or more silica particles are bonded is determined as follows: if black lines are visible between the silica particles, they are determined to be individual silica particles that are not bonded, and if no black lines are visible between the silica particles, they are determined to be one bonded silica particle. In addition, if three or more silica particles are aggregated, it is difficult to determine, so they are excluded from the measurement.
[0030] The reason why the magnification of the field emission scanning electron microscope was set to 50,000 to 200,000 times is to enable identification of the shape of each individual silica particle of 30 nm or less.
[0031] The circularity coefficient is 4πS / L, where S is the area of the secondary electron image of a silica particle taken with the above-mentioned field emission scanning electron microscope, and L is the perimeter of the secondary electron image. 2 The value is calculated as follows. The Heywood diameter is the diameter of a circle that has the same area as the secondary electron image. The major axis is the long side of a rectangle that circumscribes the secondary electron image and has the smallest area. The minor axis is the short side of a rectangle that circumscribes the secondary electron image and has the smallest area. The aspect ratio is defined as the long side of the rectangle that circumscribes the secondary electron image and has the smallest area, D L The short side of the rectangle that circumscribes the secondary electron image and has the smallest area is D S When L / D S The value is calculated as follows.
[0032] The content of metal impurities in the silica particles of the present invention is preferably 5 ppm or less, more preferably 2 ppm or less.
[0033] In polishing silicon wafers for semiconductor devices, metal impurities adhere to and contaminate the surface of the workpiece, adversely affecting the wafer characteristics and diffusing into the wafer, degrading its quality, which in turn significantly reduces the performance of semiconductor devices manufactured from such wafers.
[0034] Furthermore, when metal impurities are present in the silica particles of the present invention, a coordination interaction occurs between the acidic surface silanol groups and the metal impurities, changing the chemical properties (acidity, etc.) of the surface silanol groups and the three-dimensional environment of the silica particle surface (ease of aggregation of silica particles, etc.), thereby affecting the polishing rate.
[0035] The metal impurity content of the silica particles of the present invention is measured by inductively coupled plasma mass spectrometry (ICP-MS). Specifically, a silica sol containing 0.4 g of silica particles is accurately weighed, sulfuric acid and hydrofluoric acid are added, and the mixture is heated, dissolved, and evaporated. Then, pure water is added to the remaining sulfuric acid droplets so that the total amount is exactly 10 g to prepare a test solution, which is then measured using an inductively coupled plasma mass spectrometry device. The target metals are sodium, potassium, iron, aluminum, calcium, magnesium, zinc, cobalt, chromium, copper, manganese, lead, titanium, silver, and nickel, and the sum of the contents of these metals is the metal impurity content.
[0036] The metal impurity content of the silica particles of the present invention can be made 5 ppm or less by obtaining the silica particles by carrying out a hydrolysis reaction and a condensation reaction using an alkoxysilane as a main raw material. In the method of deionizing alkali silicate such as water glass, sodium and other impurities derived from the raw material remain, making it extremely difficult to reduce the metal impurity content of silica particles to 5 ppm or less.
[0037] The silica particles of the present invention preferably have no pores, since they have excellent mechanical strength and storage stability. The presence or absence of pores in the silica particles of the present invention is confirmed by a multipoint BET analysis using an adsorption isotherm with nitrogen as the adsorption gas.
[0038] The silica particles of the present invention preferably contain an alkoxysilane condensate as a main component, and more preferably a tetraalkoxysilane condensate as a main component, because they have excellent mechanical strength and storage stability. The main component refers to a component whose content is 50% by mass or more in 100% by mass of all components constituting the silica particles.
[0039] In order to obtain silica particles mainly composed of alkoxysilane condensates, it is preferable to use alkoxysilane as the main raw material. In order to obtain silica particles mainly composed of tetraalkoxysilane condensates, it is preferable to use tetraalkoxysilane as the main raw material. The main raw material means that it is 50% by mass or more out of 100% by mass of all raw materials constituting the silica particles.
[0040] (Method of producing silica particles) The silica particles of the present invention can be obtained, for example, by adding a solution (B) containing a tetraalkoxysilane and a solution (C) containing an alkali catalyst to a solution (A) containing water, and subjecting the tetraalkoxysilane to a hydrolysis reaction and a condensation reaction.
[0041] The solution (A) contains water. The solution (A) preferably contains a solvent other than water, since this provides excellent dispersibility of the tetraalkoxysilane in the reaction solution.
[0042] Examples of the solvent other than water in the solution (A) include methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. These solvents may be used alone or in combination of two or more. Among these solvents, monohydric alcohols are preferred, more preferably methanol and ethanol, and even more preferably methanol, because they are easy to dissolve tetraalkoxysilane, the by-products are the same as those used in the hydrolysis reaction and the condensation reaction, and they are convenient to manufacture.
[0043] The solution (A) preferably contains an alkali catalyst, since this can increase the reaction rates of the hydrolysis reaction and condensation reaction of the tetraalkoxysilane.
[0044] Examples of the alkali catalyst in the solution (A) include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkali catalysts may be used alone or in combination of two or more. Among these alkali catalysts, ammonia is preferred because it has excellent catalytic action, is easy to control the particle shape, can suppress the inclusion of metal impurities, is highly volatile, and is easy to remove after the hydrolysis reaction and the condensation reaction.
[0045] The concentration of water in solution (A) is preferably 3% by mass to 30% by mass, more preferably 5% by mass to 25% by mass, based on 100% by mass of solution (A). When the concentration of water in solution (A) is 3% by mass or more, the hydrolysis reaction rate of tetraalkoxysilane is easily controlled. Also, when the concentration of water in solution (A) is 30% by mass or less, the reaction balance between the hydrolysis reaction and the condensation reaction is good, and the particle shape is easily controlled.
[0046] The concentration of the alkali catalyst in solution (A) is preferably 0.5% by mass to 2.0% by mass, more preferably 0.6% by mass to 1.5% by mass, based on 100% by mass of solution (A). When the concentration of the alkali catalyst in solution (A) is 0.5% by mass or more, aggregation of silica particles is suppressed, and the dispersion stability of the silica particles in the dispersion is excellent. In addition, when the concentration of the alkali catalyst in solution (A) is 2.0% by mass or less, the reaction does not proceed excessively quickly, and the reaction controllability is excellent.
[0047] The concentration of the solvent other than water in the solution (A) is preferably the balance of water and the alkali catalyst.
[0048] Examples of the tetraalkoxysilane in the solution (B) include tetramethoxysilane, tetraethoxysilane, tetrapropoxysilane, and tetraisopropoxysilane. These tetraalkoxysilanes may be used alone or in combination of two or more. Among these tetraalkoxysilanes, tetramethoxysilane and tetraethoxysilane are preferred, and tetramethoxysilane is more preferred, because they undergo a fast hydrolysis reaction, are less likely to leave unreacted substances, are highly productive, and can easily produce a stable silica sol.
[0049] The raw materials for the silica particles of the present invention may be raw materials other than tetraalkoxysilane, such as low condensates of tetraalkoxysilane. However, due to their excellent reactivity, it is preferable that, out of 100% by mass of all the raw materials constituting the silica particles, tetraalkoxysilane accounts for 50% by mass or more and raw materials other than tetraalkoxysilane accounts for 50% by mass or less, and it is more preferable that tetraalkoxysilane accounts for 90% by mass or more and raw materials other than tetraalkoxysilane accounts for 10% by mass or less.
[0050] The solution (B) may contain only tetraalkoxysilane without containing a solvent, but it is preferable that the solution (B) contains a solvent, since this improves the dispersibility of the tetraalkoxysilane in the reaction liquid.
[0051] Examples of the solvent in the solution (B) include methanol, ethanol, propanol, isopropanol, and ethylene glycol. These solvents may be used alone or in combination of two or more. Among these solvents, monohydric alcohols are preferred, more preferably methanol and ethanol, and even more preferably methanol, because the solvents used in the hydrolysis reaction and the condensation reaction are the same as the by-products, and are therefore convenient for production.
[0052] The concentration of the tetraalkoxysilane in solution (B) is preferably 60% by mass to 95% by mass, more preferably 70% by mass to 90% by mass, in 100% by mass of solution (B). When the concentration of the tetraalkoxysilane in solution (B) is 60% by mass or more, the reaction liquid tends to become homogeneous. In addition, when the concentration of the tetraalkoxysilane in solution (B) is 95% by mass or less, the formation of a gel-like substance can be suppressed.
[0053] The concentration of the solvent in solution (B) is preferably 5% by mass to 40% by mass, more preferably 10% by mass to 30% by mass, in 100% by mass of solution (B). When the concentration of the solvent in solution (B) is 5% by mass or more, the generation of a gel-like substance can be suppressed. Also, when the concentration of the solvent in solution (B) is 40% by mass or less, the reaction liquid tends to become homogenous.
[0054] The addition rate of solution (B) per hour relative to the volume of solution (A) is preferably 0.05 kg / hour / L to 1.3 kg / hour / L, and more preferably 0.1 kg / hour / L to 0.8 kg / hour / L. When the addition rate of solution (B) is 0.05 kg / hour / L or more, the productivity of silica particles is excellent. Furthermore, when the addition rate of solution (B) is 1.3 kg / hour / L or less, the generation of a gel-like substance can be suppressed.
[0055] Examples of the alkali catalyst in the solution (C) include ethylenediamine, diethylenetriamine, triethylenetetraamine, ammonia, urea, ethanolamine, and tetramethylammonium hydroxide. These alkali catalysts may be used alone or in combination of two or more. Among these alkali catalysts, ammonia is preferred because it has excellent catalytic action, is easy to control the particle shape, can suppress the inclusion of metal impurities, is highly volatile, and is easy to remove after the hydrolysis reaction and the condensation reaction.
[0056] It is preferable that the solution (C) contains a solvent, since this can reduce fluctuations in the concentration of the alkali catalyst in the reaction liquid.
[0057] Examples of the solvent in the solution (C) include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. These solvents may be used alone or in combination of two or more. Among these solvents, water and monohydric alcohols are preferred, and water is more preferred, because the solvents used in the hydrolysis reaction and the condensation reaction are the same as the by-products, and they are convenient to manufacture.
[0058] The concentration of the alkali catalyst in solution (C) is preferably 0.5% by mass to 10% by mass, more preferably 1% by mass to 6% by mass, based on 100% by mass of solution (C). When the concentration of the alkali catalyst in solution (C) is 0.5% by mass or more, it is easy to adjust the concentration of the alkali catalyst in the reaction liquid from the start of the reaction to the end of the reaction. In addition, when the concentration of the alkali catalyst in solution (C) is 10% by mass or less, it is possible to reduce the fluctuation of the concentration of the alkali catalyst in the reaction liquid.
[0059] The concentration of the solvent in solution (C) is preferably 90% by mass to 99.5% by mass, more preferably 94% by mass to 99% by mass, based on 100% by mass of solution (C). When the concentration of the solvent in solution (C) is 90% by mass or more, the fluctuation of the concentration of the alkali catalyst in the reaction liquid can be reduced. Also, when the concentration of the solvent in solution (C) is 99.5% by mass or less, the concentration of the alkali catalyst in the reaction liquid can be easily adjusted from the start of the reaction to the end of the reaction.
[0060] The addition rate of solution (C) per hour relative to the volume of solution (A) is preferably 0.02 kg / hour / L to 0.5 kg / hour / L, more preferably 0.04 kg / hour / L to 0.3 kg / hour / L. When the addition rate of solution (C) is 0.02 kg / hour / L or more, the productivity of silica particles is excellent. When the addition rate of solution (C) is 0.5 kg / hour / L or less, the generation of gel-like matter can be suppressed.
[0061] The addition of solution (B) and solution (C) is preferably carried out into solution (A). By adding solution (B) and solution (C) into solution (A), when a highly volatile alkali catalyst such as ammonia is used and when a hydrolysis reaction and a condensation reaction are to be carried out at a high reaction temperature, the mixing of each component in the reaction solution is improved, abnormal reactions in the air can be suppressed, and the circularity coefficient and particle size can be easily controlled. Adding into the liquid means adding below the liquid level, and by making the supply outlet of solution (B) and the supply outlet of solution (C) below the liquid level of solution (A), solution (B) and solution (C) can be added into solution (A).
[0062] The timing of addition of solution (B) and solution (C) may be the same or may be different, such as alternately, but it is preferable that they are the same, since this reduces fluctuations in the reaction composition and does not complicate the operation.
[0063] The reaction temperature of the hydrolysis reaction and the condensation reaction is preferably 50° C. to 80° C., more preferably 55° C. to 75° C. When the reaction temperature is 50° C. or higher, it becomes easy to control the particle shape such as the Heywood diameter and the circularity coefficient. In addition, when the reaction temperature is 80° C. or lower, bumping and volatilization of the solvent can be suppressed, and fluctuations in the reaction solution can be reduced.
[0064] The concentration of water in the reaction system for the hydrolysis and condensation reactions is preferably maintained at 3% to 30% by mass, more preferably 5% to 25% by mass, based on the total amount (100% by mass) of the reaction system. When the concentration of water in the reaction system is 3% by mass or more, it is easy to control the hydrolysis reaction rate of tetraalkoxysilane. Also, when the concentration of water in the reaction system is 30% by mass or less, the reaction balance between the hydrolysis and condensation reactions is good, and the particle shape is easy to control.
[0065] The concentration of the alkali catalyst in the reaction system for the hydrolysis reaction and the condensation reaction is preferably maintained at 0.5% by mass to 2.0% by mass, more preferably at 0.6% by mass to 1.5% by mass, based on the total amount of the reaction system (100% by mass). When the concentration of the alkali catalyst in the reaction system is 0.5% by mass or more, aggregation of silica particles is suppressed, and the dispersion stability of the silica particles in the dispersion liquid is excellent. In addition, when the concentration of the alkali catalyst in the reaction system is 2.0% by mass or less, the reaction does not proceed too quickly, and the reaction controllability is excellent.
[0066] Since the method for producing silica particles of the present invention can remove unnecessary components and add necessary components, it is preferable that the method further includes the following step (1). Step (1): A step of concentrating the obtained dispersion liquid of silica particles and adding a dispersion medium
[0067] Examples of the dispersion medium include water, methanol, ethanol, propanol, isopropanol, and ethylene glycol. These dispersion media may be used alone or in combination of two or more. Among these dispersion media, water and monohydric alcohol are preferred, and water is more preferred, because they have excellent affinity with silica particles.
[0068] The method for producing silica particles of the present invention preferably further includes the following step (2) since the condensation degree of the silica particles can be increased. Step (2): A step of subjecting the dispersion of silica particles obtained in step (1) to a pressurized and heated treatment.
[0069] The pressure of the pressurized heat treatment is preferably 0.10 MPa to 2.3 MPa, more preferably 0.14 MPa to 1.0 MPa. When the pressure of the pressurized heat treatment is 0.10 MPa or more, the degree of condensation of the silica particles can be increased. When the pressure of the pressurized heat treatment is 2.3 MPa or less, the silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, cv value, and association ratio, and the dispersion stability of the silica sol is excellent.
[0070] Pressurization can be achieved by heating the silica particle dispersion in a sealed state to above the boiling point of the dispersion medium. When the silica particle aqueous dispersion is heated to 100°C or higher in a sealed state, the pressure becomes the saturated water vapor pressure at that temperature.
[0071] The temperature of the pressure and heat treatment is preferably 100° C. to 220° C., and more preferably 110° C. to 180° C. When the temperature of the pressure and heat treatment is 100° C. or higher, the degree of condensation of the silica particles can be increased. When the temperature of the pressure and heat treatment is 220° C. or lower, silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, cv value, and association ratio, and the dispersion stability of the silica sol is excellent.
[0072] The time of the pressurized heat treatment is preferably 0.25 hours to 10 hours, and more preferably 0.5 hours to 8 hours. When the time of the pressurized heat treatment is 0.25 hours or more, the degree of condensation of the silica particles can be increased. When the time of the pressurized heat treatment is 10 hours or less, the silica particles can be produced without significant changes in the average primary particle size, average secondary particle size, cv value, and association ratio, and the dispersion stability of the silica sol is excellent.
[0073] The pressurized heat treatment is preferably carried out in an aqueous dispersion because it can increase the degree of condensation of the silica particles without significantly changing the average primary particle size, the average secondary particle size, the cv value, or the association ratio.
[0074] When the pressure and heat treatment is carried out in the aqueous dispersion, the pH of the aqueous dispersion is preferably 6.0 to 8.0, more preferably 6.5 to 7.8. When the pH of the aqueous dispersion is 6.0 or more when the pressure and heat treatment is carried out in the aqueous dispersion, gelation of the silica sol can be suppressed. When the pH of the aqueous dispersion is 8.0 or less when the pressure and heat treatment is carried out in the aqueous dispersion, the degree of condensation of the silica particles can be increased without significantly changing the average primary particle size, average secondary particle size, cv value, and association ratio.
[0075] (Silica sol) The silica sol of the present invention contains the silica particles of the present invention. The silica sol may be produced by using the dispersion liquid of the silica particles of the present invention as it is, or by removing unnecessary components from the dispersion liquid of the silica particles of the present invention and adding necessary components.
[0076] The silica sol of the present invention preferably contains the silica particles of the present invention and a dispersion medium. The dispersion medium in the silica sol of the present invention can be, for example, water, methanol, ethanol, propanol, isopropanol, ethylene glycol, etc. These dispersion mediums in the silica sol can be used alone or in combination of two or more. Among these dispersion mediums in the silica sol, water and monohydric alcohol are preferred, and water is more preferred, because they have excellent affinity with silica particles.
[0077] The content of silica particles in the silica sol of the present invention is preferably 3% by mass to 50% by mass, more preferably 4% by mass to 40% by mass, and even more preferably 5% by mass to 30% by mass, based on the total amount of the silica sol (100% by mass). When the content of silica particles in the silica sol of the present invention is 3% by mass or more, the polishing rate for a polished object such as a silicon wafer is excellent. In addition, when the content of silica particles in the silica sol of the present invention is 50% by mass or less, the aggregation of silica particles in the silica sol or polishing composition can be suppressed, and the storage stability of the silica sol or polishing composition is excellent.
[0078] The content of the dispersion medium in the silica sol of the present invention is preferably 50% by mass to 97% by mass, more preferably 60% by mass to 96% by mass, and even more preferably 70% by mass to 95% by mass, based on the total amount of the silica sol (100% by mass). When the content of the dispersion medium in the silica sol of the present invention is 50% by mass or more, the aggregation of silica particles in the silica sol or polishing composition can be suppressed, and the storage stability of the silica sol or polishing composition is excellent. In addition, when the content of the dispersion medium in the silica sol of the present invention is 97% by mass or less, the polishing rate for the polished object represented by silicon wafer is excellent.
[0079] The content of silica particles and dispersion medium in the silica sol of the present invention can be set within a desired range by removing unnecessary components from the components in the obtained dispersion liquid of silica particles and adding necessary components.
[0080] In addition to the silica particles and the dispersion medium, the silica sol of the present invention may contain other components, such as an oxidizing agent, a preservative, an antifungal agent, a pH adjuster, a pH buffer, a surfactant, a chelating agent, and an antibacterial and biocide, as necessary, within the range that does not impair the performance of the silica sol. In particular, it is preferable to include an antibacterial biocide in the silica sol, since this provides excellent storage stability of the silica sol.
[0081] Examples of antibacterial biocides include hydrogen peroxide, ammonia, quaternary ammonium hydroxide, quaternary ammonium salt, ethylenediamine, glutaraldehyde, hydrogen peroxide, methyl p-hydroxybenzoate, sodium chlorite, etc. These antibacterial biocides may be used alone or in combination of two or more. Among these antibacterial biocides, hydrogen peroxide is preferred because it has excellent affinity with silica sol. Biocides also include those commonly referred to as bactericides.
[0082] The content of the antibacterial biocide in the silica sol of the present invention is preferably 0.0001% by mass to 10% by mass, more preferably 0.001% by mass to 1% by mass, based on the total amount of the silica sol (100% by mass). When the content of the antibacterial biocide in the silica sol of the present invention is 0.0001% by mass or more, the storage stability of the silica sol is excellent. When the content of the antibacterial biocide in the silica sol of the present invention is 10% by mass or less, the inherent performance of the silica sol is not impaired.
[0083] The pH of the silica sol of the present invention is preferably 6.0 to 8.0, more preferably 6.5 to 7.8. When the pH of the silica sol of the present invention is 6.0 or more, the dispersion stability is excellent and the aggregation of silica particles can be suppressed. Also, when the pH of the silica sol of the present invention is 8.0 or less, dissolution of silica particles is prevented and the long-term storage stability is excellent. The pH of the silica sol of the present invention can be adjusted to a desired range by adding a pH adjuster.
[0084] (polishing composition) The polishing composition of the present invention comprises the silica sol of the present invention. The polishing composition of the present invention preferably contains the silica sol of the present invention and a water-soluble polymer.
[0085] The water-soluble polymer enhances the wettability of the polishing composition to the object to be polished, such as a silicon wafer. The water-soluble polymer is preferably a polymer having a functional group with high water affinity, and the functional group with high water affinity has a high affinity with the surface silanol group of the silica particles, so that the silica particles and the water-soluble polymer are stably dispersed in the polishing composition in a closer vicinity. Therefore, when polishing the object to be polished, such as a silicon wafer, the effects of the silica particles and the water-soluble polymer function synergistically.
[0086] Examples of the water-soluble polymer include cellulose derivatives, polyvinyl alcohol, polyvinylpyrrolidone, copolymers having a polyvinylpyrrolidone skeleton, and polymers having a polyoxyalkylene structure.
[0087] Examples of cellulose derivatives include hydroxyethyl cellulose, hydrolyzed hydroxyethyl cellulose, hydroxypropyl cellulose, hydroxyethyl methyl cellulose, hydroxypropyl methyl cellulose, methyl cellulose, ethyl cellulose, ethyl hydroxyethyl cellulose, and carboxymethyl cellulose.
[0088] An example of the copolymer having a polyvinylpyrrolidone skeleton is a graft copolymer of polyvinyl alcohol and polyvinylpyrrolidone.
[0089] Examples of polymers having a polyoxyalkylene structure include polyoxyethylene, polyoxypropylene, and copolymers of ethylene oxide and propylene oxide.
[0090] These water-soluble polymers may be used alone or in combination of two or more. Among these water-soluble polymers, cellulose derivatives are preferred, and hydroxyethyl cellulose is more preferred, because they have high affinity with the surface silanol groups of silica particles and act synergistically to impart good hydrophilicity to the surface of the polished object.
[0091] The weight-average molecular weight of the water-soluble polymer is preferably 1,000 to 3,000,000, more preferably 5,000 to 2,000,000, and even more preferably 10,000 to 1,000,000. When the weight-average molecular weight of the water-soluble polymer is 1,000 or more, the hydrophilicity of the polishing composition is improved. When the weight-average molecular weight of the water-soluble polymer is 3,000,000 or less, the affinity with silica sol is excellent, and the polishing rate for the polished object, typically a silicon wafer, is excellent.
[0092] The weight-average molecular weight of the water-soluble polymer is measured by size exclusion chromatography using a 0.1 mol / L NaCl solution as the mobile phase, in terms of polyethylene oxide.
[0093] The content of the water-soluble polymer in the polishing composition is preferably 0.02% by mass to 10% by mass, more preferably 0.05% by mass to 5% by mass, based on the total amount of the polishing composition (100% by mass). When the content of the water-soluble polymer in the polishing composition is 0.02% by mass or more, the hydrophilicity of the polishing composition is improved. Furthermore, when the content of the water-soluble polymer in the polishing composition is 10% by mass or less, the aggregation of silica particles during preparation of the polishing composition can be suppressed.
[0094] In addition to the silica sol and the water-soluble polymer, the polishing composition of the present invention may contain other components, such as a basic compound, a polishing accelerator, a surfactant, a hydrophilic compound, a preservative, an antifungal agent, a pH adjuster, a pH buffer, a surfactant, a chelating agent, and an antibacterial and biocide, as necessary, within the range that does not impair the performance of the composition.
[0095] In particular, it is preferable to include a basic compound in the polishing composition, since it is possible to perform chemical polishing (chemical etching) by applying a chemical action to the surface of an object to be polished, such as a silicon wafer, and because a synergistic effect with the surface silanol groups of the silica particles can improve the polishing speed of an object to be polished, such as a silicon wafer.
[0096] Examples of the basic compound include organic basic compounds, alkali metal hydroxides, alkali metal hydrogen carbonates, alkali metal carbonates, and ammonia. These basic compounds may be used alone or in combination of two or more. Among these basic compounds, ammonia, tetramethylammonium hydroxide, tetraethylammonium hydroxide, ammonium hydrogen carbonate, and ammonium carbonate are preferred because they are highly soluble in water and have excellent affinity with silica particles and water-soluble polymers, and ammonia, tetramethylammonium hydroxide, and tetraethylammonium hydroxide are more preferred, with ammonia being even more preferred.
[0097] The content of the basic compound in the polishing composition of the present invention is preferably 0.001% by mass to 5% by mass, more preferably 0.01% by mass to 3% by mass, based on the total amount of the polishing composition (100% by mass). When the content of the basic compound in the polishing composition is 0.001% by mass or more, the polishing speed of the object to be polished, such as a silicon wafer, can be improved. In addition, when the content of the basic compound in the polishing composition is 5% by mass or less, the stability of the polishing composition is excellent.
[0098] The pH of the polishing composition of the present invention is preferably 8.0 to 12.0, more preferably 9.0 to 11.0. When the pH of the polishing composition is 8.0 or more, the aggregation of silica particles in the polishing composition can be suppressed, and the dispersion stability of the polishing composition is excellent. When the pH of the polishing composition of the present invention is 12.0 or less, the dissolution of silica particles can be suppressed, and the stability of the polishing composition is excellent. The pH of the polishing composition of the present invention can be adjusted to a desired range by adding a pH adjuster.
[0099] The polishing composition of the present invention can be obtained by mixing the silica sol of the present invention and, if necessary, a water-soluble polymer and other components. However, taking into consideration storage and transportation, the composition may be prepared at a high concentration and then diluted with water or the like immediately before polishing.
[0100] (polishing method) The polishing method of the present invention is a method comprising a step of polishing with a polishing composition containing the silica sol obtained by the method for producing a silica sol of the present invention.
[0101] As the polishing composition, it is preferable to use the polishing composition of the present invention described above. A specific example of the polishing method is a method in which the surface of a silicon wafer is pressed against a polishing pad, the polishing composition of the present invention is dropped onto the polishing pad, and the surface of the silicon wafer is polished.
[0102] (Method of manufacturing semiconductor wafers) The method for producing a semiconductor wafer of the present invention includes the polishing method of the present invention, and the specific polishing method is as described above. Examples of semiconductor wafers include silicon wafers and compound semiconductor wafers.
[0103] (Method of manufacturing semiconductor devices) The method for producing a semiconductor device of the present invention includes the polishing method of the present invention, and the specific polishing method is as described above.
[0104] (Application) The silica particles of the present invention and the silica sol of the present invention can be suitably used for polishing purposes.The silica particles of the present invention and the silica sol of the present invention can be suitably used for polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing (chemical mechanical polishing) in the flattening process when manufacturing integrated circuits, polishing synthetic quartz glass substrates used for photomasks and liquid crystals, polishing magnetic disk substrates, etc., and can be suitably used for polishing silicon wafers and chemical mechanical polishing.
[0105] The silica particles of the present invention are silica particles with large circularity coefficient, so when used as a composite material with resins, they impart transparency and water repellency to the resins, and improve dispersibility and mixability to improve the processability of the composite material.Therefore, the silica particles of the present invention can be suitably used as a hard coat agent, paint, and ceramic binder. EXAMPLES
[0106] The present invention will be described in more detail below using examples. However, the present invention is not limited to the description of the following examples as long as it does not deviate from the gist of the present invention.
[0107] (Measuring the shape of silica particles) The dispersion of silica particles obtained in the examples and comparative examples was diluted 5000 times with ultrapure water, and 5 μL of the diluted dispersion of silica particles was dropped onto a silicon substrate and dried. Next, using a field emission scanning electron microscope (model name "S-5200 type", Hitachi High-Technologies Corporation, FE-SEM), the silicon substrate was irradiated with an electron beam at an acceleration voltage of 5 kV, and a secondary electron image was taken at a magnification of 50,000 to 200,000 so that the total number of silica particles was 80 or more. The Heywood diameter, major axis, minor axis, circularity coefficient, and aspect ratio of all silica particles were measured, and the average value and standard deviation were measured.
[0108] In measuring the shape of the silica particles, the field emission scanning electron microscope photographs were imported into an image analysis type particle size distribution measurement software (software name "Mac-View Ver. 4", manufactured by Mountec Co., Ltd.).
[0109] The shape of the silica particles was determined as described below. Whether or not two or more silica particles were bonded was determined as individual silica particles that were not bonded when black lines were visible between the silica particles, and as one silica particle that was bonded when no black lines were visible between the silica particles. In addition, when three or more silica particles were aggregated, it was difficult to determine, so they were excluded from the measurement.
[0110] [Example 1] 34.2 parts by mass of pure water, 188.3 parts by mass of methanol, and 8.8 parts by mass of 29% by mass aqueous ammonia were mixed to obtain solution (A1). Solution (B1) obtained by mixing 100 parts by mass of tetramethoxysilane and 33.3 parts by mass of methanol, and solution (C1) obtained by mixing 25.0 parts by mass of pure water and 2.2 parts by mass of 29% by mass aqueous ammonia were added to the solution (A1) at a constant rate over 103 minutes. During the addition, the reaction solution was stirred while maintaining the temperature of the reaction solution at 70°C. After the addition was completed, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 70°C.
[0111] The temperature of the obtained silica particle dispersion was increased to remove methanol and ammonia while adjusting the liquid volume by adding pure water so that the silica particle content was approximately 20 mass %, thereby obtaining a silica particle dispersion with a silica particle content of approximately 20 mass %. The evaluation results of the obtained silica particles are shown in Table 1.
[0112] [Example 2] The same operation as in Example 1 was carried out except that the temperature of the reaction liquid was set to 60° C., to obtain a dispersion liquid of silica particles with a silica particle content of about 20 mass %. The evaluation results of the obtained silica particles are shown in Table 1.
[0113] [Example 3] 40.6 parts by mass of pure water, 207.6 parts by mass of methanol, and 5.2 parts by mass of 29% by mass aqueous ammonia were mixed to obtain solution (A3). Solution (B3) obtained by mixing 100 parts by mass of tetramethoxysilane and 17.6 parts by mass of methanol, and solution (C3) obtained by mixing 21.5 parts by mass of pure water and 2.1 parts by mass of 29% by mass aqueous ammonia were added to the solution (A3) at a constant rate over 93 minutes. During the addition, the reaction solution was stirred while maintaining the temperature of the reaction solution at 50°C. After the addition was completed, the reaction solution was stirred for another 30 minutes while maintaining the temperature of the reaction solution at 50°C.
[0114] The temperature of the obtained silica particle dispersion was increased to remove methanol and ammonia while adjusting the liquid volume by adding pure water so that the silica particle content was approximately 20 mass %, thereby obtaining a silica particle dispersion with a silica particle content of approximately 20 mass %. The evaluation results of the obtained silica particles are shown in Table 1.
[0115] [Example 4] 34.9 parts by mass of pure water, 204.4 parts by mass of methanol, and 13.1 parts by mass of 29% by mass aqueous ammonia were mixed to obtain solution (A4). Solution (B4) in which 100 parts by mass of tetramethoxysilane and 17.6 parts by mass of methanol were mixed, and solution (C4) in which 19.4 parts by mass of pure water and 5.3 parts by mass of 29% by mass aqueous ammonia were mixed were added to the solution (A4) at a constant rate over 94 minutes. During the addition, the reaction solution was stirred while maintaining the temperature at 70°C. After the addition was completed, the reaction solution was stirred for another 30 minutes while maintaining the temperature at 70°C.
[0116] The temperature of the obtained silica particle dispersion was increased to remove methanol and ammonia while adjusting the liquid volume by adding pure water so that the silica particle content was approximately 20 mass %, thereby obtaining a silica particle dispersion with a silica particle content of approximately 20 mass %. The evaluation results of the obtained silica particles are shown in Table 1.
[0117] [Comparative Example 1] A commercially available dispersion of silica particles (product name "PL-1", manufactured by Fuso Chemical Co., Ltd.) was used as is. The evaluation results of the silica particles used are shown in Table 1.
[0118] [Comparative Example 2] A commercially available dispersion of silica particles (product name "PL-2", manufactured by Fuso Chemical Co., Ltd.) was used as is. The evaluation results of the silica particles used are shown in Table 1.
[0119] [Comparative Example 3] A commercially available dispersion of silica particles (product name "PL-2L", manufactured by Fuso Chemical Co., Ltd.) was used as is. The evaluation results of the silica particles used are shown in Table 1.
[0120] [Comparative Example 4] 21.4 parts by mass of pure water, 95.2 parts by mass of methanol, and 3.7 parts by mass of 29% by mass aqueous ammonia were mixed to obtain solution (A'4). Solution (B'4) obtained by mixing 100 parts by mass of tetramethoxysilane and 17.6 parts by mass of methanol, and solution (C'4) obtained by mixing 21.9 parts by mass of pure water and 3.2 parts by mass of 29% by mass aqueous ammonia were added to the solution (A'4) at a constant rate over 94 minutes. During the addition, the reaction solution was stirred while maintaining the temperature at 42°C. After the addition was completed, the reaction solution was stirred for another 30 minutes while maintaining the temperature at 42°C.
[0121] The temperature of the obtained silica particle dispersion was increased to remove methanol and ammonia while adjusting the liquid volume by adding pure water so that the silica particle content was approximately 20 mass %, thereby obtaining a silica particle dispersion with a silica particle content of approximately 20 mass %. The evaluation results of the obtained silica particles are shown in Table 1.
[0122] [Comparative Example 5] The same operation as in Example 1 was carried out, except that solution (B1) and solution (C1) were added dropwise from above the liquid level of solution (A1) rather than into the solution (A1). However, a large amount of silica particles adhered to the inner wall of the reaction vessel, the stirring blades, etc., making it difficult to continue the operation thereafter.
[0123] [Table 1]
[0124] As can be seen from Table 1, the silica particles obtained in Examples 1 to 4 have a larger average circularity coefficient, a smaller average Heywood diameter, an average major axis, an average minor axis, and an average aspect ratio, and their standard deviations are also smaller, compared to the commercially available silica particles of Comparative Examples 1 to 3 and the silica particles obtained in Comparative Example 4. This indicates that the silica particles have a smaller variation in particle shape and particle size.
[0125] The silica particles obtained in Examples 1 to 4 are expected to suppress secondary aggregation and have excellent dispersion stability because of the small variation in particle shape and particle size. In addition, the silica particles obtained in Examples 1 to 4 are expected to provide a polishing composition having a smooth surface and excellent stability of polishing performance because of the small variation in particle shape and particle size.
[0126] In addition, the dispersion of silica particles obtained in Example 1 was similarly evaluated 9 months after production, and the dispersion showed almost no change, and secondary aggregation was hardly observed, indicating excellent dispersion stability.
[0127] Although the present invention has been described in detail and with reference to specific embodiments, it is apparent to those skilled in the art that various changes and modifications can be made without departing from the spirit and scope of the present invention. This application is based on a Japanese patent application (Patent Application No. 2020-11471) filed on January 28, 2020, the contents of which are incorporated herein by reference. [Industrial Applicability]
[0128] The silica particles of the present invention and the silica sol of the present invention can be suitably used for polishing purposes.The silica particles of the present invention and the silica sol of the present invention can be suitably used for polishing semiconductor materials such as silicon wafers, polishing electronic materials such as hard disk substrates, polishing (chemical mechanical polishing) in the flattening process when manufacturing integrated circuits, polishing synthetic quartz glass substrates used for photomasks and liquid crystals, polishing magnetic disk substrates, etc., and can be suitably used for polishing silicon wafers and chemical mechanical polishing.
Claims
1. Silica particles having an average circularity coefficient of 0.90 or more, a standard deviation of the circularity coefficient of 0.05 or less, and an average aspect ratio of 1.20 or less, as measured by a field emission scanning electron microscope.
2. 2. The silica particles according to claim 1, having an average Heywood diameter of 20 nm or less as measured by a field emission scanning electron microscope.
3. 3. The silica particles according to claim 1, which have an average aspect ratio of 1.20 or less as measured by a field emission scanning electron microscope.
4. 3. The silica particles according to claim 2, wherein the standard deviation of the Heywood diameter is 3.00 nm or less.
5. 4. The silica particles according to claim 3, wherein the standard deviation of the aspect ratio is 0.15 or less.
6. The silica particles according to any one of claims 1 to 5, wherein the content of metal impurities is 5 ppm or less.
7. The silica particles according to any one of claims 1 to 6, which are mainly composed of a tetraalkoxysilane condensate.
8. A silica sol comprising the silica particles according to any one of claims 1 to 7.
9. A polishing composition comprising the silica sol according to claim 8.
10. A polishing method comprising a step of polishing with the polishing composition according to claim 9.
11. A method for producing a semiconductor wafer, comprising a step of polishing the semiconductor wafer with the polishing composition according to claim 9.
12. A method for producing a semiconductor device, comprising a step of polishing with the polishing composition according to claim 9.
Citation Information
Patent Citations
Preparation method of silica sol controllable in grain size
CN105731468A
Production of silica particle
JP1987260712A
Production of fine spherical silica
JP1988074911A
Inorganic uniform fine sphere and preparation thereof
JP1992154605A
Production of silica sol
JP1994316407A